Faktor-Faktor yang Mempengaruhi Perempuan pada Perusahaan Retail (Study Kasus Alfamart)di Kota Pekanbaru - Bahari, Aza; Putro, Tri Sukirno; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the city of Pekanbaru in July to August 2014.The purpose of this study was to determine the effect of educational level, age structure and the level of wages of women working in a retail establishment (Alfamart case study). This study used primary data and analyzes are used the descriptive analysis. Sample population of this study was all female workers Alfamart in Pekanbaru. The sample in this study using Cochran formula as many as 60 people Alfamart female workers in the city of Pekanbaru, while sampling technique using simple random sampling. The results of the study come to the conclusion that the educational level and age negative effect on women's work in a retail establishment (Alfamart) in Pekanbaru, meaning that the higher the level of education and age of the respondent the less women working in a retail establishment (Alfamart) in the city of Pekanbaru and vice versa. And positive effect on the wage rate of women working in a retail establishment (Alfamart) means that the higher the wage rate, the more women working in a retail establishment (Alfamart) in the city of Pekanbaru and vice versa.Keywords: Level of Education, Age, Wage Rates, and Labor Alfamart Women.